2018
DOI: 10.1007/s00439-017-1862-z
|View full text |Cite|
|
Sign up to set email alerts
|

The CAPOS mutation in ATP1A3 alters Na/K-ATPase function and results in auditory neuropathy which has implications for management

Abstract: Cerebellar ataxia, areflexia, pes cavus, optic atrophy and sensorineural hearing impairment (CAPOS) is a rare clinically distinct syndrome caused by a single dominant missense mutation, c.2452G>A, p.Glu818Lys, in ATP1A3, encoding the neuron-specific alpha subunit of the Na+/K+-ATPase α3. Allelic mutations cause the neurological diseases rapid dystonia Parkinsonism and alternating hemiplegia of childhood, disorders which do not encompass hearing or visual impairment. We present detailed clinical phenotypic info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 52 publications
6
19
0
Order By: Relevance
“…A recent electrophysiological study reported an accelerated release of Na ϩ toward the extracellular side in the CAPOS mutant (17), which is in good agreement with the present electrophysiological findings and is further underscored by our finding of an increased E 2 P/E 1 P ratio in the biochemical experiments ( Fig. 9).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A recent electrophysiological study reported an accelerated release of Na ϩ toward the extracellular side in the CAPOS mutant (17), which is in good agreement with the present electrophysiological findings and is further underscored by our finding of an increased E 2 P/E 1 P ratio in the biochemical experiments ( Fig. 9).…”
Section: Discussionsupporting
confidence: 93%
“…The reduced affinity for cytoplasmic Na ϩ , the weaker voltage dependence, and the stronger K ϩ inhibition of the CAPOS mutant compared with WT, on the other hand, provide important clues to the pathophysiology of the mutant, as explained above. The previous study (17) moreover pointed to an observed increase of the inward proton leak through the CAPOS mutant as a probable disease-causing mechanism. The leak current is also increased by ␣2 Na ϩ ,K ϩ -ATPase C-terminal mutations causing familial hemiplegic migraine (36), as well as by C-terminal deletions (37,38), and certain mutations causing aldosterone producing adenomas (39).…”
Section: Discussionmentioning
confidence: 84%
“…Individuals with mutated variants of the ATP1A3 gene present a syndromic phenotype including cerebellar ataxia, areflexia, pes cavus, optic atrophy and SNHL, summarized in the acronym CAPOS syndrome [90]. In the ten families where CAPOS syndrome has been described to date, only the specific heterozygous mutation c.2452G > A in exon 4 has been consistently reported [91][92][93][94][95][96][97][98].…”
Section: Postsynaptic Synaptopathiesmentioning
confidence: 99%
“…It generally starts with the sudden onset of cerebellar ataxia and febrile illness. Recurrent episodes have also been reported 11 . Hearing loss is a common symptom in patients with CAPOS syndrome, however the nature and prognosis of the disease can vary.…”
Section: Introductionmentioning
confidence: 90%